Palaeoecology and palaeoethology of the Plio-Pleistocene genus Cervalces (Cervidae, Mammalia) in Eurasia - BREDA, Marzia (2008)
The paleoecology and palaeoethology of the Eurasian species of the extinct genus Cervalces are inferred by morpho-functional comparison with its living relative Alces alces. Most of the characters that differentiate A. alces from all other deer are shared by Cervalces: the peculiar morphology of the cheek teeth; the shape of the premaxillary tips; the long legs; the peculiar morphology of the femur; the extreme fusion of the tarsal elements; the peculiar articular surface of the third phalanx. The most important morpho-skeletal differences between the two genera are: the long nasal bones contiguous with the short premaxillary bones in Cervalces (whereas Alces has very short nasal bones not contiguous with the extremely long premaxillary bones); the stronger and more backward inclined ascending ramus of the mandible in Cervalces; the much wider span of antlers in Cervalces because of its longer beams; the different shape of the antler palmation; the stronger proximal ulna/radius connection in Cervalces. The close similarity between the morphological features of the dentition and postcranial skeleton of Alces and Cervalces suggests that they could have chewed the same kind of food and moved in the same way. However, their quite different facial skeleton and antler shape, should have played some ecological role, even if interpretation of such a role is difficult. Such wide antlers may possibly have served as display organs in open ground. Nevertheless, the common idea that Cervalces should have lived in more open environments than living moose is probably an oversimplification.